Review of differential diagnosis and management of spasmodic dysphonia. Issue 3 (June 2016) - Whurr, Renata; Lorch, Marjorie
Abstract : Purpose of review: The recent literature on spasmodic dysphonia is reviewed with regard to pathogenesis, differential diagnosis, treatment options, audits, and current methods of management. Recent findings: Advances in technology have enabled clinicians to better understand the connection between brain and laryngeal function and dysfunction. Refinements in imaging and genetic investigation techniques have led to advances in the understanding of the underlying mechanism of this neurolaryngeal disorder. Development of diagnostic assessment tools and measures of quality of life hold the potential to improve treatment and care. Summary: Fifty articles published between 2014 and 2015 were selected for this review. The sources were drawn from several clinical specialties: 54% come under the scope of laryngology, 32% from neurology, and 14% from other areas. It remains poorly understood, misdiagnosed, and underdiagnosed. Its identification, diagnosis, treatment selection, and coordination of care require an expert specialist multidisciplinary team. More training is required to help people who have this chronic and psychosocially disabling voice disorder, which impinges on all aspects of their lives. Spasmodic dysphonia is now classified as a 'rare' disease in the United States. This designation will assist in international standards of diagnosis, assessment, treatment, and management.